Rancang Bangun Aplikasi Wisata Edukasi Berbasis Android dan QR Code pada Geosite Hutan Kerangas Cendil Belitung Timur - Sumarno; Kurniawan, Rudy; Gusa, Rika Favoria (ELECTRON Jurnal Ilmiah Teknik Elektro, 2023)
The Cendil Heath Forest Geosite is located in Cendil Village, East Belitung Regency which is part of the Belitong Geopark. On this tour, visitors go around the forest with a tour guide who will explain the details of the flora according to the signboard. Besides making it difficult for guides, this system makes the information obtained by Tourists is not optimal. This study aims to design and build an educational tourism application based on Android and QR code. By building an Android application that has a QR Code scanner feature, detailed flora information in the QR Code will appear so that the information will be delivered optimally. The system created consists of a website system that uses the CodeIgniter framework and an Android system that uses the Kotlin programming language. Testing was carried out with a questionnaire to 30 people with details of 3 Administrators, 5 Managers, and 22 Application Users. The test results show that the Application User is satisfied with the application made both in terms of appearance, convenience, and application functionality. Meanwhile, the response of Managers and Administrators is satisfied with the website that is made both in terms of appearance, ease of use, and application functionality.